O09.2 Declines in chlamydia-associated PID at sshs in england since 2007: what might this tell us about chlamydia control?. (14th July 2019) - Horner, Paddy; Davis, Grahame; Soldan, Kate
Abstract : Background: In 1998 the United Kingdom Chief Medical Officer recommended action to reduce the prevalence and morbidity associated with chlamydial infection. The introduction of NAAT testing from 2003 and the roll-out of the National Chlamydia Screening Programme (NCSP) in England from 2004 to 2008 (all regions participating) resulted in large increases in chlamydia screening and diagnoses: 2.3 million tests were reported in 2010 among 15 to 24 year-olds, equivalent to 44% of women and 24% of men in this age group. We investigated rates of diagnoses of pelvic inflammatory disease (PID) in women attending specialist sexual health services (SSHS) since 2007. Methods: Data were extracted from the GUMCAD surveillance system from 2007–2017. To explore the effect of changes in access to SSHS over this time, total number of attendances were also extracted and changes in PID diagnoses were compared to those of a symptomatic clinical presentation with no active control programme, vaginosis/vaginitis (bacterial vaginosis, candidiasis, trichomoniasis). Results: Between 2007 and 2017 PID diagnoses decreased by 18%. Chlamydia-associated-PID (CT-PID) diagnoses decreased by 46%, and the% of PIDs associated with CT fell from 14.7% (∼2, 400) to 9.7% (∼1, 300). GC-associated-PID increased 34% (to ∼300). Decreases were greater in under 25s and in years up to 2011/12. Attendances by women under 25 increased over this time, and there was a 6% increase in diagnoses of vaginitis/vaginosis, with CT-PID decreasing by 49% relative to vaginitis/vaginosis. Conclusion: There has been a marked decline in diagnoses of CT-PID, and all PID, at SSHS subsequent to the introduction of wide-spread chlamydia screening. This has occurred despite an increase in attendances at SSHS and access for symptomatic women (vaginosis/vaginitis). Further work will explore trends by region and in general practice, and will determine whether CT-PID rates might be a metric for the success of chlamydia control. Disclosure: No significant relationships.